Mapping Permafrost Features that Influence the Hydrological Processes of a Thermokarst Lake on the Qinghai‐Tibet Plateau, China. (21st January 2014) - Pan, Xicai; You, Yanhui; Roth, Kurt; Guo, Lei; Wang, Xinbing; Yu, Qihao
ABSTRACT Climate warming has been observed for some time in the permafrost regions on the Qinghai‐Tibet Plateau (QTP), China, resulting in active layer thickening, shrinkage or expansion of thermokarst lakes, and reduced permafrost extent. Little is known, however, about the hydrological processes near thermokarst lakes and their influences on lake development. We employed ground‐penetrating radar (GPR) profiling, topographic mapping and drilling to explore the interaction between hydrological processes and thermokarst lake development at a site on the QTP. The GPR data and borehole water‐level measurements revealed spatio‐temporal variation of the frost table and soil water storage, and indicated the main direction of subsurface flow through soil on hillslopes near the lake. The measurements hinted at the self‐organised formation of lateral flow channels at the thawing frost table near the lake. The ensuing recharge of the lake is balanced by drainage from the deepest end of the lake, down the topographic gradient, as ascertained by coring and lake bed mapping. Such a process‐based qualitative understanding is crucial for assessing the impact of climate change, in conjunction with the local topography and hydrogeology, on the evolution of thermokarst lakes on the QTP. Copyright © 2014 John Wiley & Sons, Ltd.